2018
DOI: 10.3390/en11112926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coal Deformation on Different-Phase CO2 Permeability in Sub-Bituminous Coal: An Experimental Investigation

Abstract: Coal deformation is one of the leading problems for carbon dioxide (CO2) sequestration in coal seams especially with respect to different-phase CO2 injection. In this paper, a series of core flooding tests were conducted under different confining stresses (8–20 MPa), injection pressures (1–15 MPa), and downstream pressures (0.1–10 MPa) at 50 °C temperature to investigate the effects of coal deformation induced by adsorption and effective stress on sub-critical, super-critical, and mixed-phase CO2 permeability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The Datong coalfield is located in the north of Shanxi Province, China (Figure 1), with a total area of 1827 km 2 from 39°52′ to 40°10′ north latitude and 112°49′32″ to 113°9′30″ west longitude. 29 It consists of two coal-bearing strata: the upper Jurassic coal-bearing stratum with 60.8 Gt of coal reserves and the lower Carboniferous and Permian coal-bearing stratum with 369.1 Gt of coal reserves. It is a main large-scale coalfield in China, as well as one of the potential CO 2 sequestration sites.…”
Section: Methodsmentioning
confidence: 99%
“…The Datong coalfield is located in the north of Shanxi Province, China (Figure 1), with a total area of 1827 km 2 from 39°52′ to 40°10′ north latitude and 112°49′32″ to 113°9′30″ west longitude. 29 It consists of two coal-bearing strata: the upper Jurassic coal-bearing stratum with 60.8 Gt of coal reserves and the lower Carboniferous and Permian coal-bearing stratum with 369.1 Gt of coal reserves. It is a main large-scale coalfield in China, as well as one of the potential CO 2 sequestration sites.…”
Section: Methodsmentioning
confidence: 99%
“…When CO 2 transitions from gaseous to supercritical state, the swelling of the coal matrix only increases by about 6%. 59 Therefore, there is no need to worry about more ScCO 2 being adsorbed and causing a significant deformation of the coal matrix, leading to a substantial decrease in permeability.…”
Section: Comparison Between Gaseous Co 2 and Supercritical Comentioning
confidence: 99%
“…Although CO 2 has a stronger ability to cause coal expansion after adsorption, experimental evidence has shown that the majority of volume deformation occurs during the gaseous CO 2 adsorption stage, accounting for approximately 94%. When CO 2 transitions from gaseous to supercritical state, the swelling of the coal matrix only increases by about 6% . Therefore, there is no need to worry about more ScCO 2 being adsorbed and causing a significant deformation of the coal matrix, leading to a substantial decrease in permeability.…”
Section: Comparison Between Gaseous Co2 and Supercritical Co2mentioning
confidence: 99%